Residual Forest Biomass in Pinus Stands: Accumulation and Biogas Production Potential - Alexandros Eftaxias; Evangelia Anna Passa; Christos Michailidis; Christodoulos Daoutis; Apostolos Kantartzis; Vasileios Diamantis (Energies, 2022)
Lignocellulosic biomass is an abundant resource that can be valorized for the production of bioenergy. However, studies aiming to quantify the amount of biogas production potential per km forest road are scarce in the literature. In this study, fresh pine needles, pine needle litter, pine branches, and pine bark were digested in batch reactors under mesophilic conditions after a grinding/milling pre-treatment. All samples were collected from a low-altitude Mediterranean Pinus forest (North Greece) adjacent to a category G forest road with a gentle slope. The methane yield of fresh pine needles was between 115 and 164 NmL g−1 volatile solids (VS), depending on the Pinus tree size. Pine needle litter produced a significantly lower methane yield (between 58 and 77 NmL g−1 VS), followed by pine bark (85 NmL g−1 VS) and pine branches (138 NmL g−1 VS). Considering the quantity of pine needle litter accumulated on adjacent forest roads (600 ± 200 g m−2), it was possible to calculate the biomethane production potential per km of forest road (up to 500 Nm3 km−1) if the biomass collected was disposed of at an anaerobic digestion facility. The results of the study demonstrate that residual forest biomass represents an additional resource for bioenergy production. Moreover, harvesting residual forest biomass can decrease the incidence of devastating summer forest fires and their disastrous consequences for the environment, the economy, and the local populations.